(untitled) (Medico Legal Update, 2020)
Road Traffic Accidents are one of the leading causes of morbidity and mortality in the world. The etiological factors may be classified into human and environmental out of which human factors are much more responsible for number of accidents. This study was carried out on Road Traffic Accidents cases reported to casualty department of Muzaffarnagar Medical College, Muzaffarnagar (U.P) from 1st July 2016 to 30th June 2017. The main objectives of the study were to know the causes and factors responsible for the accidents. Data were collected and analyzed. A Total of 416 cases were included in the study. Human error is responsible for accidents in 78% of cases in which drivers were at fault in 57.0% of cases followed by the pedestrians and passengers of vehicles who were responsible for 18% and 3.0% cases respectively. Faults in vehicles and poor weather accounted for accidents 8.0% & 7.8% of total cases respectively. Bad roads were responsible for accidents in 4.0% of total cases. None of the driver or passengers of the vehicles was wearing helmets or seat belts which are a very alarming trend. The important human factors responsible for accidents were over speeding, rash driving, violation of traffic rules, carelessness, wrong crossing, playing on roads, alcohol intake, fatigue or sleepiness.